The ayahuasca gives you your art (2014)
To Paolo del Águila, descending from the ashaninka people, creativity is a gift of the plants. During his first visionary experience, ayahuasca personified in the body of an ancient lady presented him with painting brushes and a personal style, releasing him from the disputes and conventionalism he had faced in Pucallpa city art school. Since then, painting and life are one to him and his objective as an artist is to communicate to the public the spiritual experiences he underwent in a domain of existence normally invisible which he aims to render visible to their eyes.